Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kedisiplinan Kerja Pegawai Pada UD. Sari Bumi Di Sragen - Wahono, Tri; , Jati Waskito, SE., MM (2017)
This study aims to determine determine the effect of motivation and work environment on work of dicipline UD. Sari Bumi. The sample in this study are employees at UD. Sari Bumi totaling 50 respondents. The sampling technique in this research is purposive sampling and convenience sampling. Data analysis method used is validity, reability and test multiple linear regression analysis with t-test, F, and the coefficient of determination (R2). The findings indicate that either partially or simultaneously motivation and work environment on work of dicipline UD. Sari Bumi. At determinant coefficient (R2) is variable work motivation and work environment on the work of dicipline is 57,8%. Keywords: Work of Motivation, Work of Evironment, Work of Dicipline.